2020
DOI: 10.1089/hum.2020.049
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus and Hematopoietic Stem Cells: The Potential of Adeno-Associated Virus Hematopoietic Stem Cells in Genetic Medicines

Abstract: Adeno-associated virus (AAV)-based vectors have transformed into powerful elements of genetic medicine with proven therapeutic efficacy and a good safety profile. Over the years, efforts to transduce hematopoietic stem cells (HSCs) with AAV2 vectors have, however, been challenging. While there was evidence that AAV2 delivered vector genomes to primitive, quiescent, multipotential, self-renewing, in vivo engrafting HSCs, transgene expression was elusive. In this study, we review the evolution of AAV transductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The modification of target cells with the gene of interest can face various challenges. For example, adeno-associated virus vectors do not effectively transduce HSCs due to blocks to nuclear entry, uncoating and second-strand synthesis [ 110 ]. Pseudotyping lentiviral vectors with a VSV-G envelope leads to broad cell tropism although primary human resting T cells, and CD34+ cells are not effectively transduced due to a lack of or inadequate expression of the LDLR receptor, through which it gains entry into the cell [ 111 ].…”
Section: Ex Vivo Gene Therapymentioning
confidence: 99%
“…The modification of target cells with the gene of interest can face various challenges. For example, adeno-associated virus vectors do not effectively transduce HSCs due to blocks to nuclear entry, uncoating and second-strand synthesis [ 110 ]. Pseudotyping lentiviral vectors with a VSV-G envelope leads to broad cell tropism although primary human resting T cells, and CD34+ cells are not effectively transduced due to a lack of or inadequate expression of the LDLR receptor, through which it gains entry into the cell [ 111 ].…”
Section: Ex Vivo Gene Therapymentioning
confidence: 99%
“…We have recently shown that AAV editing vectors belonging to clade F mediate exclusively HR-based, highly accurate and seamless, and efficient genome editing in human cells and mice without the requirement for exogenous nucleases ( Figure 2D ) ( Smith et al, 2018 ). These vectors include a family of novel, naturally occurring AAVs isolated from healthy human hematopoietic stem cells (HSCs), termed AAVHSC ( Smith et al, 2014 ; Chatterjee et al, 2020 ). AAVHSC editing was found to be precise and efficient, with no on-target insertion/deletion mutations and no evidence of genomic scarring or incorporation of residual viral sequences, including the ITRs.…”
Section: Aavhsc Editing Vectorsmentioning
confidence: 99%
“…It has been shown that AAVHSC-mediated gene insertion can correct the disease phenotype in a PKU mouse model. 93 A phase I/II clinical trial has recently been initiated using AAVHSC15 in patients with late-onset PKU ( Table 1 ).…”
Section: Viral Vectorsmentioning
confidence: 99%